PENGARUH E-SERVICE QUALITY TERHADAP KEPUASAN PENGGUNA APLIKASI GRAB DI KOTA KUPANG - Juita L D Bessie; Lea Susanti Taek (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study aims to determine and analyze (1) the partial effect of e-service quality (website design, reliability, responsiveness, security/privacy, fulfillment, personalization, information, and empathy) on Grab Application users in Kupang City and (2) the effect of e-service quality (website design, reliability, responsiveness, security/privacy, fulfillment, personalization, information, and empathy) simultaneously on Grab Application users in Kupang City. The number of samples is 100 respondents, and the sampling technique used is purposive sampling. Data was collected using questionnaires. The data analysis techniques used are descriptive quantitative, multiple linear regression analysis, and hypothesis testing through t-tests and F-test using the SPSS 26 application. The results of the descriptive analysis show that the respondents gave a very good perception of the e-service quality implemented by Grab. The results of the t-test and F-test show that, partially and simultaneously, e-service quality (website design, reliability, responsiveness, security/privacy, fulfillment, personalization, information, empathy) has a significant effect on customer satisfaction. Based on the adjusted R2 value, it shows the contribution of the e-service quality variable to customer satisfaction, which is 89.4%, and 10.6% is influenced by other variables outside the focus of this study. The other variable is efficiency, which can be taken into consideration by further researchers in addition to the existing variables. Keywords: e-Service Quality; Website Design; Reliability; Responsiveness; Security/Privacy; Fulfillment; Personalization; Information; Empathy; Customer Satisfaction